The Abe restoration contemporary Japanese politics and reformation - Mark, Craig (Lanham Lexington Books, 2016)
"This book analyzes contemporary Japanese politics, charting the return of Prime Minister Shinzo Abe's domestic political dominance and his economic and foreign policy agenda. It is an up-to-date account and critique of the progress, obstacles, and far-reaching consequences of one of the most important periods in recent Japanese history"--Provided by publisher.
Origins of the Abe restoration -- Abe's political restoration -- Abenomics -- Restoration of strategic policy -- Continuing the Abe restoration : after the 2014 election -- The "War Bills" debate -- The Abe restoration to 2016 -- Conclusion: The legacy of the Abe restoration.
Includes bibliographical references (pages 149-164) and index.
Keywords: Abe, Shinzo -- 1954-.; Abe, Shinzo -- 1954- -- Political and social views; Abe, Shinzo -- 1954- -- Influence; Prime ministers -- Japan -- Biography; Japan -- Politics and government -- 1989-.; Japan -- Economic policy -- 1989-.; Japan -- Foreign relations -- 1989-.